Spontaneous coronary artery dissection: novel pathophysiological insights from histological and ultrastructural tissue analysis. (25th November 2020) - Margaritis, M; Saini, F; Baranowska, A; Parsons, S; Vink, A; Budgeon, C; Alcock, N; Wagner, B; Samani, N; Robertus, J.L; Von Der Thusen, J; Sheppard, M; et al.
Abstract: Introduction: Spontaneous coronary artery dissection (SCAD) is a cause of acute coronary syndromes and rarely sudden cardiac death (SCD). SCAD is characterised by medial false lumen haematoma formation and periadventitial inflammatory cell infiltrate. Although SCAD has been linked to connective tissue disorders, its pathophysiology remains poorly understood and the role of inflammation unknown. Purpose: We sought to establish the definitive histopathological features of SCAD and explore pathophysiological mechanisms through assessment of dermal connective tissue ultrastructure. Methods: N=36 SCD cases diagnosed as SCAD on autopsy were identified in pathology archives at four international centres. Their demographic and clinical characteristics were compared with n=359 survivors recruited in a SCAD survivors cohort. Haematoxylin & eosin sections were examined under light microscope. Immunohistochemistry (IHC) was employed for quantification of inflammatory cell infiltrate (CD68, CD3) and vasa vasorum density (CD31) of SCAD cases (n=20) compared to age- and sex-matched controls (n=10). Dermal extracellular matrix components (EMC) of n=32 SCAD survivors and n=16 healthy volunteers (HV) were compared using electron microscopy (EM). Results: The autopsy series cases were more likely to be male (p=0.0256) and had higher incidence of left main stem (p=0.0475) and proximal left anterior descending (p<0.001) disease compared to SCAD survivors. N=24 (66%) of SCAD autopsy case showed no evidence of myocardial necrosis. N=17 (47%) showed mild-moderate atherosclerotic changes but no features of fibromuscular dysplasia. There were no differences in vasa vasorum density between SCAD and control cases (A). The degree of inflammatory cell infiltrate varied greatly but significantly higher than controls (B), comprising CD68+ macrophages, eosinophils and CD3+ positive T-cells. There was a statistically significant association (p=0.006) between the degree of inflammatory cell infiltrate and the length of time from onset of symptoms to death (Panel C), as well as significantly (p<0.001) denser inflammatory cell infiltrate adjacent to the dissection plane (D, exemplary sections E&F). EM revealed no differences between SCAD and HV in dermal fibroblast size & activity or elastin size & damage indicators, but possible changes in subgroups with more extreme clinical phenotype or pregnancy-related SCAD (G). Conclusions: To our knowledge this is the largest SCAD pathology case series so far. We show for the first time that periadvential inflammation in SCAD appears to be time-dependent and localising to the dissected coronary segment, suggesting healing response to injury rather than causal contribution. We found no evidence to suggest increased vasa vasorum density is pathophysiologically important. Connective tissue changes were only linked to a small proportion of cases. These novel findings may have important implications for the management of SCAD patients. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): British Heart Foundation, Leicester NIHR Biomedical Research Centre